Targeting of temozolomide using magnetic nanobeads: an in vitro study - Berna Gürten; Elçin Yenigül; Ali Demir Sezer; Cem Altan; Seyda Malta (Universidade de São Paulo, 2020)
Temozolomide, a chemotherapeutic drug that is often administered for the treatment of brain cancer has severe side effects and a poor aqueous solubility. In order to decrease the detrimental effect of the drug over healthy cells, a novel drug delivery vehicle was developed where the therapeutic drug was encapsulated within the hydrophobic cavities of b-CD modified magnetite nanoparticles, which are embedded in chitosan nanobeads prepared by salt addition. In-vitro studies have shown that the magnetic properties of the novel delivery vehicle are adequate for targeted drug delivery applications under an external magnetic field. Additionally, an increase in the amount of chitosan was shown to exhibit a strong shielding effect over the magnetic properties of the delivery vehicle, which lead to deterioration of the amount of captured drug at the targeted area, suggesting a delicate balance between the amounts of constituents composing the drug delivery vehicle.